Pengaruh penggunaan aplikasi wordwall terhadap motivasi belajar peserta didik di Madrasah Ibtidaiyah - Indah Dwi Cahyani; Siti Nurul Fadhilah (Sagita Academia Journal, 2026)
This study aims to examine the effect of using the Wordwall application on students’ learning motivation in Madrasah Ibtidaiyah through a literature-based approach. The background of this study is the low level of students’ learning motivation, which is often influenced by the use of less interactive and less engaging learning media in the classroom. Therefore, the integration of digital learning media such as Wordwall is expected to create a more interactive and enjoyable learning environment. This research employed a qualitative approach using a literature review method. The data used in this study were secondary data obtained from various sources, including scientific journals, articles, and books accessed through academic databases such as Google Books and other relevant references. Data were collected through documentation techniques and analyzed descriptively to identify patterns, relationships, and findings from previous studies without conducting direct field research. The results indicate that the use of Wordwall-based learning media has a positive effect on students’ learning motivation, as reflected in increased engagement, participation, and interest in learning activities. Furthermore, the interactive features of Wordwall contribute to creating a more enjoyable and student-centered learning environment. Thus, it can be concluded that Wordwall is an effective interactive learning medium to enhance students’ learning motivation in Madrasah Ibtidaiyah based on existing literature.